2004
DOI: 10.1073/pnas.0407197101
|View full text |Cite
|
Sign up to set email alerts
|

Melyrid beetles ( Choresine ): A putative source for the batrachotoxin alkaloids found in poison-dart frogs and toxic passerine birds

Abstract: Batrachotoxins are neurotoxic steroidal alkaloids first isolated from a Colombian poison-dart frog and later found in certain passerine birds of New Guinea. Neither vertebrate group is thought to produce the toxins de novo, but instead they likely sequester them from dietary sources. Here we describe the presence of high levels of batrachotoxins in a little-studied group of beetles, genus Choresine (family Melyridae). These small beetles and their high toxin concentrations suggest that they might provide a tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 15 publications
0
124
0
2
Order By: Relevance
“…In the likelihood and Bayesian phylogenies, P. kirhocephalus is monophyletic as well, however, the support is poor, and parsimony analyses do not unequivocally support this monophyly. The confusing variation within this species has been long recognized (Beehler et al, 1986) and results from three highly differentiated genetic groups within P. kirhocephalus that distinguish the north-coast, south-coast, and West Papuan Island clades (Dumbacher et al, 2004). Other analyses directed at biogeography continue to support further splitting P. kirhocephalus (Dumbacher, Fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the likelihood and Bayesian phylogenies, P. kirhocephalus is monophyletic as well, however, the support is poor, and parsimony analyses do not unequivocally support this monophyly. The confusing variation within this species has been long recognized (Beehler et al, 1986) and results from three highly differentiated genetic groups within P. kirhocephalus that distinguish the north-coast, south-coast, and West Papuan Island clades (Dumbacher et al, 2004). Other analyses directed at biogeography continue to support further splitting P. kirhocephalus (Dumbacher, Fig.…”
Section: Discussionmentioning
confidence: 91%
“…This in no way precludes that the toxins have an anti-ectoparasite function as well. Instead, we suggest that the toxins are likely ''broad spectrum" poisons that offer a variety of advantages (Dumbacher et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…P. nigrescens, a mildly toxic species, is sister to all true Pachycephala whistlers, whereas the mildly toxic P. cristatus is closely related to Aleadryas rufinucha, a species distantly related to the Pachycephala radiation. P. ferrugineus, which has often been found to be devoid of batrachotoxins (Dumbacher et al 2004), is closely related to the Australo-Papuan Colluricincla shrike-thrushes, which were also demonstrated to have traces of batrachotoxins (Dumbacher et al 2004). I. kowaldi is not closely related to any Pitohui species.…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that the bird Ifrita kowaldi contained a similar spectrum of batrachotoxins as Pitohui. At the time, however, no reliable phylogenetic framework was available to determine the relationship between Ifrita and Pitohui, and thus whether the ability to tolerate this toxin in the body is restricted to a specific avian lineage (Dumbacher et al 2004).…”
Section: Introductionmentioning
confidence: 99%